Spatial and temporal distribution of perfluoroalkyl substances (PFAS) detected after an aqueous film forming foam (AFFF) spill - Miranda, Daniele A.; Abessa, Denis M.S. [UNESP]; Moreira, Lucas B. [UNESP]; Maranho, Luciane A. [UNESP]; Oliveira, Lauriney G. [UNESP]; Benskin, Jonathan P.; Leonel, Juliana (Elsevier, 2024)
In 2015, > 460,000 L of aqueous film-forming foam (AFFF) and fire suppressors containing per- and polyfluoroalkyl substances (PFAS) were used to combat a fire at a petrochemical fuel storage terminal in the Port of Santos (Brazil). Sediments from seven sites were sampled repeatedly from 2 weeks to 1 year after the fire (n = 30). Ʃ15PFAS concentrations ranged from 115 to 15,931 pg g−1 dry weight (dw). Perfluorooctane sulfonic acid (PFOS) was the most frequently detected compound with concentrations ranging from 363 to 4517 (average = 1603) pg g−1dw to <47.1 to 642 (average = 401) pg g−1 dw, followed by perfluorohexanoic acid (PFHxA) (from 38.8 to 219 (average = 162) pg g−1 dw after 15 days and from <20.8 to 161 (average = 101) pg g−1 dw one year later). Together, the hydrodynamics and fire events documented in the region were important features explaining the spread of PFAS.
Keywords: Aqueous film forming foam (AFFF); PFAS; PFHxA; Santos Estuarine System; Subtropical estuary